Huchimingia, a new genus segregated from Millettia (Leguminosae, Millettieae) based on morphological and molecular evidence - Song, Zhu-Qiu; Li, Shi-Jin; Mattapha, Sawai (Phytotaxa, 2022)
Millettia Wight & Arn. is a heterogeneous genus within the tribe Millettieae (Leguminosae) and has long been used as a repository to accommodate all undistinctive species of the tribe with elastically dehiscent pods. Millettia sect. Podocarpae Dunn is representative of the heterogeneous genus. This section includes five Asian species that have a unique combination of characters that distinguishes them from all other species of the genus, including the deciduous tree habit, conspicuous buds covered with scales, pseudoracemes or pseudopanicles with very indistinct brachyblasts, two flowers per brachyblast, conspicuous large bracts, ebracteolate calyx, well-developed hypanthium, stipitate ovary, and flat, stipitate and dehiscent pods. Our molecular phylogeny based on plastid matK and nuclear ribosomal ITS sequences also suggested the section is clearly monophyletic, separate from other congeneric species, and is most closely related to Antheroporum Gagnep. with inflated, vacuous pods and Ohashia X.Y. Zhu & R.P. Zhang with indehiscent flat pods. Therefore, we propose a new genus, Huchimingia Z.Q. Song & Shi J. Li, to accommodate this distinct section.